The Relationship between Husband's Assistance and Pain During Birth at BPM Zahriah Stabat District in 2022 - Maya Sari (Institute of Computer Science (IOCS), 2022)
Labor pain is very important to pay attention to because pain in labor can weaken uterine contractions and result in prolonged labor and even death. Efforts that can be made to reduce pain are by providing the closest person, namely assistance from the husband, because the effect of feeling pain in every mother in labor can be minimized by making the husband as a delivery companion. This study aims to find out about the relationship between husband's mentoring and pain during childbirth at BPM Zahriah, Stabat District in 2022. The results of the study showed that the husband's assistance at BPM Zahriah, Stabat sub-district was in the good category (79.17%), the category of pain during labor at BPM Zahriah, Stabat sub-district was (50.0%). The results of the analysis with a value of p = 0.005 so that the conclusion is that there is an effect of the relationship between husband's assistance and pain during childbirth in post partum mothers at BPM Zahriah, Stabat District in 2022.Data was collected using a questionnaire and for pain measurement using a checklist. The conclusion in this study is that there is a relationship between husband's assistance and pain in childbirth at BPM Zahriah, Stabat District in 2022. Suggestions in this study are expected for BPM Zahriah to continue to encourage and support Husband Assistance for mothers in labor to reduce pain during childbirth.